The Impact of Community-Based Testing Sites and Gift Incentives on COVID-19 Testing Uptake in Maryland, April 29 – May 9, 2021. Issue 2 (February 2023) - Turbyfill, Caitlin; Thomas, Isabel; Agravat, Namita; Prasher, Joanna M; Nett, Randall J; Stevens, Melody; Ricaldi, Jessica N; Dunams, Tambra M; Brickhouse-Frazier, Latasha; Carter, Melissa D; Gebru, Yonathan; King, Ashley; et al.
Purpose: Information on incentives for COVID-19 testing is needed to understand effective practices that encourage testing uptake. We describe characteristics of those who received an incentive after performing a rapid antigen test. Design: Cross-sectional descriptive analysis of survey data. Setting: During April 29–May 9, 2021, COVID-19 rapid antigen testing was offered in 2 Maryland cities. Sample: Convenience sample of 553 adults (≥18 years) who tested and received an incentive; 93% consented to survey. Measures: Survey questions assessed reasons for testing, testing history, barriers, and demographics. Analysis: Robust Poisson regressions were used to determine characteristic differences based on testing history and between participants who would re-test in the future without an incentive vs participants who would not. Results: The most common reasons for testing were the desire to be tested (n = 280; 54%) and convenience of location (n = 146; 28%). Those motivated by an incentive to test (n = 110; 21%) were 5.83 times as likely to state they would not test again without an incentive, compared to those with other reasons for testing (95% CI: 2.67-12.72, P < .001). Critical Limitations: No comparative study group. Conclusion: Results indicate internal motivation and convenience were prominent factors supporting testing uptake. Incentives may increase community testing participation, particularly among people who have never tested. Keywords COVID-19, pandemic, incentives, health behavior, community testing.